Development of STEM-Based Science Educational Game Using Scratch to Train Computational Thinking Skill for Socondary School Students - Wulandari, Tiara Dwi; Listaji*, Prasetyo; Sulaiman, Tajularipin; Wan Jaafar, Wan Marzuki; Abdul Rahim, Suzieleez Syrene (Jurnal Pendidikan Sains Indonesia, 2024)
Computational Thinking Skills (CTS) possessed by Indonesian students are not yet in the good category. This skills have not been integrated in learning. This is in accordance with the results of preliminary research at SMP Negeri 8 Semarang that CTS are a new concept for science teachers, including learning media used by teachers have not helped train students' CTS. Through preliminary research, it is known that science teachers give a positive response to the use of technology-based learning media that train students' CTS, one of which is a science educational game using Scratch. The purpose of this study was to analyze the validity and determine the profile of students' CTS after using science educational games. The type of research used is development research with the ADDIE model. The instruments used are expert validation questionnaires, student readability sheets, and tests after using science education games. The results showed that the science education game was valid with a score of 0.89. The readability of science education games is very good with a score of 96.7. Through the test, it was found that the percentage of students with high computational thinking ability was 56.66%, medium 26.66%, and low 16.66%. Based on the research that has been done, it can be concluded that the science education game is valid and can train CTS of junior high school students.